The Implications of Religious Charismatic Leadership on Worker Engagement: The Part That Commitment to the Company Plays - Afrida Afrida; Ramon Zamora; Lukmanul Hakim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The basic objective of this study is to investigate, via the prism of organisational commitment, the connection between Religious Charismatic leadership and employee engagement. In order to find out how the research variables were related to each other, this quantitative study used AMOS-SEM, a data analysis tool. A positive and statistically significant effect of religious charismatic leadership on staff engagement was found. Organisational commitment acts as a robust mediator between Religious Charismatic leadership and workforce engagement. This research of human resource management at KSPPS BMT NU Kabupaten Lamongan provides a new perspective as a case study.